2020
DOI: 10.1371/journal.pone.0230723
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes prevalence by HbA1c and oral glucose tolerance test among HIV-infected and uninfected Tanzanian adults

Abstract: BackgroundThe burden of diabetes is increasing in sub-Saharan Africa, including among people living with HIV. We assessed the prevalence of diabetes and the roles of HIV, antiretroviral therapy (ART) and traditional risk factors among adults in Tanzania. MethodsWe analysed diabetes-relevant baseline data from 1,947 adult participants in the CICADA study in Mwanza, Tanzania: 655 HIV-uninfected, 956 HIV-infected ART-naïve, and 336 HIV-infected persons on ART. WHO guidelines for haemoglobin A1c (HbA1c) and oral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 40 publications
4
64
0
Order By: Relevance
“…The study population and main methods have been reported elsewhere [12]. Briefly, participants who were recruited in previous tuberculosis and HIV nutritional supplementation trials in Mwanza from 2006 to 2013 (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study population and main methods have been reported elsewhere [12]. Briefly, participants who were recruited in previous tuberculosis and HIV nutritional supplementation trials in Mwanza from 2006 to 2013 (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Data on demographics and NCDs risk factors were collected based on the WHO STEPS manual questionnaire [17]. According to previously reported analysis, of the lifestyle factors, only physical activity was associated with diabetes [12], so was the only such variable included here. Less than 600 MET (metabolic equivalent of tasks) minutes per week was considered as being physically inactive [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous blood for HbA1c was drawn from those who had fasted, and participants were then given 82.5 g of dextrose monohydrate (equivalent to 75 g of anhydrous glucose) diluted in 250 ml of drinking water to drink within 5 minutes for OGTT. Blood for OGTT glucose was collected after 30 minutes and 2 hours, and glucose was measured with a point-of-care machine (HemoCue 201RT, Ä ngelholm, Sweden) [19]. HbA1c was measured with a point-of-care device (HemoCue HbA1c 501), which uses a boronate affinity assay to separate the glycated hemoglobin fraction from the non-glycated fraction; the instrument is calibrated to harmonize with HPLC method (HbA1c 501 Analyzer, Operating Manual).…”
Section: Diabetes-related Measurementsmentioning
confidence: 99%
“…The study was exploratory and had funds to obtain hemoglobinopathy information only on a sub-set of CICADA participants. In the entire CICADA cohort, diabetes was diagnosed using HbA1c in 13% of participants, and an additional 17% were pre-diabetic [19]. Assuming a higher prevalence of PD/DM among participants without hemoglobinopathies of 32%, with 80% statistical power, the study could detect PD/DM among participants with hemoglobinopathies of 19%, with at least 80% power.…”
Section: Sample Size and Power Considerationsmentioning
confidence: 99%